Validating information system success in the electronic government context - Hussein, Ramlah; Abdul Karim, Nor Shahriza (IIUM Press, 2009)
information system success has been widely discussed in the past two decades. As systems and technologies are being improved and developed, discussion on their effectiveness and evaluation on their success have been continuously debated by researchers, scholars, and practitioners throughout the years. The development of IS success model by De Lone and Mc Lean had overcome some of the issues in evaluating and assessing IS used in several contexts. The purpose of the present study is to empirically validate the De Lone and Mc Lean's IS Success Model in a non-volitional usage context in the electronic government setting. To achieve this objective, survey questionnaire were gathered from 201 users from four Malaysian e-government central agencies. The study used four dimensions - system quality, information quality, perceived usefulness, and user satisfaction which constitute the up-stream part of the original model. Five hypotheses were developing showing the relationship of the variables investigated. Using structural equation modeling techniques, the study found to be the model reasonably well and this suggest that the IS success model was also to be empirically valid in a non-volitional context such as in this case, the electronic government context.